2012
DOI: 10.1002/jmri.23701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatic adenoma and focal nodular hyperplasia with gadoxetic acid

Abstract: Purpose-To characterize imaging features of histologically proven hepatic adenoma (HA) as well as histologically and/or radiologically proven focal nodular hyperplasia (FNH) using delayed hepatobiliary MR imaging with 0.05mmol/kg gadoxetic acid. Materials and Methods-Five patients with sixHAs with histological correlation were retrospectively identified on liver MRI studies performed with gadoxetic acid, and T1-weighted imaging acquired during the delayed hepatobiliary phase. Additionally, 23 patients with 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…59,61 The central hypointense core of FNHs is generally larger in extent than the central scar observed in dynamic phases. 60,62 Even in such cases, however, the peripheral hyperintense rim on hepatocyte phase might imply an uptake ability of the lesion, i.e., FNH rather than HA (Fig. 4b).…”
Section: Distinguishing Between Focal Nodular Hyperplasia (Fnh) and Hmentioning
confidence: 99%
See 3 more Smart Citations
“…59,61 The central hypointense core of FNHs is generally larger in extent than the central scar observed in dynamic phases. 60,62 Even in such cases, however, the peripheral hyperintense rim on hepatocyte phase might imply an uptake ability of the lesion, i.e., FNH rather than HA (Fig. 4b).…”
Section: Distinguishing Between Focal Nodular Hyperplasia (Fnh) and Hmentioning
confidence: 99%
“…4a, b). 59,60 On the other hand, hepatocyte phase images of HAs generally show hypointensity. A central scar, an anomalous portal area with abundant loose connective tissue, is a well known and speciˆc imagingˆnding of FNH but not observed in all cases.…”
Section: Distinguishing Between Focal Nodular Hyperplasia (Fnh) and Hmentioning
confidence: 99%
See 2 more Smart Citations
“…Zech et al [25] reported enhancement in the hepatobiliary phase in the 90% of FNH examined in their series where only a minority of lesions showed no enhancement or peripheral enhancement. The presence of biliary canaliculi, even if not functioning, leads to a "slower excretion in comparison to the surrounding parenchyma", and this gadoxetic acid retention explains the hyperintense appearance of FNH [26] (Figures 1 and 2). Nevertheless, atypical lesions are very difficult to diagnose, even using Gd-EOB-DTPA.…”
Section: Evaluation Of Hepatic Adenoma and Focal Nodular Hyperplasiamentioning
confidence: 99%